Identification of Mangrove Molluscs in Forest of Toniku West Halmahera District of South Jailolo North Maluku Province - Tyas Asrining Pertiwi, Reni; Widiyanti, Endah Sri; Abdulah, Farid Muhammad; Surya, Sunelsya (Jurnal Moluska Indonesia, 2024)
The people of Toniku Village exploite the mangrove forest to meet their daily needs, especially to get protein needs when the weather at sea is not possible to catch fish. Mollusks as a source of protein that provides nutrition for coastal communities, especially the people of Toniku Village. This study aims to identify mollusks found in the Mangrove Forest of Toniku Village. Sampling method using purposive sampling. Biota sampling was carried out at five stations in rows three times on a plot size of 10 m x 10 m. The sample preserves and is identified based on the literature and World Register of Marine Spesies. The data analysis used was qualitative. The results obtained were two classes, four families, and six mollusk species. The mollusk found in the mangrove forest of Toniku Village were Ellobium aurisjudae, Cerithidea quoyii, Telescopium telescopium, Neripteron violaceum, Vittina cumingiana, and Geloina erosa.